Cover Feature: Photocatalytic Giese‐Type Reaction with Alkylsilicates Bearing C, O‐Bidentate Ligands (Chem. Eur. J. 22/2021). Issue 22 (12th February 2021) - Morofuji, Tatsuya; Matsui, Yu; Ohno, Misa; Ikarashi, Gun; Kano, Naokazu
Abstract : A photocatalytic Giese‐type reaction using alkylsilicates bearing C, O‐bidentate ligands as stable alkyl radical precursors has been reported. Not only primary, secondary, and tertiary alkyl radicals but also elusive methyl radicals could be generated using the present reaction system. The generated radicals were trapped by electron‐deficient olefins bearing various functional groups to give the desired alkyl adducts. Theoretical calculations provide an insight on the facile generation of methyl radicals from methylsilicate bearing C, O‐bidentate ligands. More information can be found in the Full Paper by T. Morofuji, N. Kano et al. on page 6713 .